Rapamycin ameliorates chronic intermittent hypoxia and sleep deprivation-induced renal damage via the mammalian target of rapamycin (mTOR)/NOD-like receptor protein 3 (NLRP3) signaling pathway. Issue 3 (1st March 2022) - Liu, Wei; Zhao, Dong; Wu, Xiaofeng; Yue, Fang; Yang, Haizhen; Hu, Ke
ABSTRACT: Rapamycin inhibits the activation of NOD-like receptor protein 3 (NLRP3) by regulating the mammalian target of rapamycin (mTOR) to treat obstructive sleep apnea-related renal injury. Sleep deprivation (SD) and chronic intermittent hypoxia (CIH) mouse models were used to assess the effects of autophagy in vivo. Compared with the control, SD, and CIH groups, the SD+CIH group had lower body weight and higher levels of blood urea nitrogen (BUN), creatinine, and urinary albumin (U-Alb) (P < 0.05); renal injury and oxidative damage occurred in the SD+CIH group, the kidney cell nucleus ruptured, and morphological structure of the cells was unclear in the SD+CIH group. The SD+CIH group demonstrated increased apoptosis compared with the control, SD, and CIH groups using Western blot analysis. Compared to the control, SD, and CIH groups, the SD+CIH group showed a higher degree of microtubule-associated protein light chain 3 staining. Compared to the SD+CIH group, BUN, creatinine, and U-Alb levels decreased, and apoptosis increased in the SD+CIH+rapamycin group, and the structure of the kidney after rapamycin treatment was well preserved. The mTOR expression was increased in the kidneys of the SD+CIH group. The NLRP3, Gasdermin D (GMDSD), interleukin (IL)-18, IL-1β, and cleaved-caspase-1 protein levels were higher in the SD+CIH group than the SD+CIH+rapamycin group, and the NLRP3, GMDSD, IL-18, IL-1β, and cleaved-caspase-1 mRNA levels were higher in the SD+CIH group than the SD+CIH+rapamycin group. Following rapamycin treatment, pyroptosis was suppressed. Rapamycin ameliorates renal damage by inhibiting the mTOR/NLRP3 signaling pathway. Graphical abstract: uf0001